Boundedness and Compactness of a Certain Class of Matrix Operators with Variable Limits of Summation - Temirkhanova, Ainur; Beszhanova, Aigul (Eurasian Mathematical Journal, 2020)
Necessary and sufficient conditions for the boundedness and compactness of the matrix operator of the form (Af)n = ∑β(n)k=α(n) an,kfk, from lp,v to lq,u when 1 < p ≤ q <∞ are given.